Misselection and related errors in Malay writing among French students - Abdul Halim, Hazlina; Ang, Lay Hoon; Majtanova, Miroslava; Mansor, Nor Shahila (Universiti Putra Malaysia Press, 2016)
Error analysis is one of the ways to study and correct learners’ mistakes in vocabulary and syntax in the process of leaning a foreign language. Hence, this study aims to analyse misselection and related errors made by French students in their learning Malay as a foreign language with regard to the writing skills. The study utilized quantitative and qualitative method of data collection, by applying the definition of misselection errors by Dulay, Burt and Krashen (1982) and misformation errors by James (1998) to the analysis. A total of 10 French respondents participated in this study. The task consisted of the administration of the four writing task. The study discovered the most dominant error produced by French students in their Malay written tasks were misselection on lexis (52%), misselection error on affix/ suffix (16%) and misselection errors on the phrases (11%). As a result of this preliminary study, it is hoped that learners can acquire a better understanding of the Malay language; and future study can help classify the errors that learners made and how they could overcome them.